Towards a natural classification and backbone tree for Graphostromataceae, Hypoxylaceae, Lopadostomataceae and Xylariaceae - Daranagama, Dinushani A (2017)
Species and generic recognition in the orderXylariales has been uncertain due to lack of molecular datafrom authentic cultures, as well as overlapping morphologicalcharacteristics. In this study, we revise the familiesGraphostromataceae, Hypoxylaceae, Lopadostomataceaeand Xylariaceae in Xylariales. Our study is based on DNAsequence data derived from living cultures of fresh isolates,data from GenBank and morphological observation of typeand worldwide herbarium specimens. We also collectednew specimens from Germany, Italy and Thailand. Combinedanalyses of ITS, LSU, RPB2 and b-tubulin sequencedata were used to reconstruct the molecular phylogeny ofthe above families. Generic and familiar boundariesbetween these families are revised and presented in anupdated combined phylogenetic tree. We accept six generain Graphostromataceae, 19 genera in Hypoxylaceae, fourin Lopadostomataceae and 37 genera in Xylariaceae. Fivegenera previously treated in Xylariaceae are placed inAmphisphaeriales genera incertae sedis and seven generaare placed in Xylariales genera incertae sedis. Two generaare placed in Sordariomycetes genera incertae sedis, whilefour genera are placed as Xylariomycetidae genera incertaesedis. Three genera are considered as doubtful. Barrmaeliaand Cannonia, presently included in Xylariaceae aretransferred to Diatrypaceae and Coniochaetales respectively,based on their morphology and phylogeny. Areolosporaand Myconeesia are excluded from Xylariaceaeand synonymized with Phaeosporis and Anthostomellarespectively. Updated descriptions and illustrations areprovided for all taxa with notes provided on each genus.Excluded and doubtful genera are listed with notes on theirtaxonomy and phylogeny. Taxonomic keys are providedfor all revised families with morphological details forgenera within the families.